A Geoarchaeological Survey of the Marine Extension of the Roman Archaeological Site Villa del Pezzolo, Vico Equense, on the Sorrento Peninsula, Italy. Issue 3 (29th March 2016) - Aucelli, Pietro; Cinque, Aldo; Giordano, Francesco; Mattei, Gaia
Abstract : The Roman Villa on the Marina di Equa (Vico Equense, Sorrento Peninsula, Italy), built in the first century A.D., is an important coastal site where the geological effects of the A.D. 79 eruption of Vesuvius are combined with archaeological remains, thus representing an interaction of both human and natural events. At this site, a patrician Roman villa, located at the outlet of a steep V‐shaped valley on the northern flank of a ridge in the Lattari Mountains, was completely destroyed by the A.D. 79 eruption and by subsequent mud/debris flows and floods. During these catastrophic events, the villa was rebuilt twice, in the second and third centuries A.D., as shown by archaeological evidence on the beach. A marine geophysical survey was conducted to study the unexplored portion of this archaeological site. A geographical information system (GIS) analysis of integrated geophysical survey data has identified and mapped (in two and three dimensions) the major underwater archaeological structures on and below the seabed in the villa harbor. A map of the ancient port of the Roman villa has been created by correlating the submerged remains with the construction phases of the villa.